E-Monogeo: A Problem-Based Interactive Media Approach for Geography Students - Hayadi, Shinta Putri Dwika (Future Space: Studies in Geo-Education, 2025)
Geography learning in the 21st century is not limited to memorizing facts and concepts, but must be closely related to the real life of students, and the development of geography learning media that can connect learning materials with current events is very important. Learning media must meet various standards to support effective, interactive, and student-centered teaching and learning processes. Developing or creating new learning media requires data analysis on the needs of students, teachers, or curriculum. In the results of the needs analysis of SMAN 1 Gondang Nganjuk, both students and teachers need new learning media to guide students in problem-solving learning. Therefore, the objectives of this study are (1) to develop E-Monogeo learning media based on problem-based learning (2) to determine the feasibility of E-Monogeo media (3) to determine the practicality of E-Monogeo media (4) knowing the effectiveness of E-Monogeo media. E-Monogeo learning media is designed by prioritizing innovative learning with an approach that emphasizes solving real world problems. The product underwent rigorous content and media validation, achieving high feasibility ratings (>88%) from experts, confirming its construct validity. Furthermore, a quasi-experimental implementation at SMAN 1 Gondang demonstrated the medium's pedagogical efficacy: the experimental group utilizing E-Monogeo achieved significantly higher learning outcomes (Mean=88) compared to the control group (Mean=66). These findings suggest that integrating digital gamification with PBL effectively transforms passive learning into active problem solving, offering a scalable solution for 21st century geography education.